2010
DOI: 10.1243/09544100jaero687
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic inlet buzz margin control of ducted rockets

Abstract: The maximum performance of a supersonic inlet will be achieved when operating as close as possible to its buzz boundary. In order to maintain high performance without crossing the buzz boundary, an active buzz margin predictor and controller is necessary. The goal of a control system is to acquire inlet buzz margin and maintain it as the designated value and predict inlet buzz before it occurs and then take some measures to buzz mitigation or inlet restart. The inlet buzz boundary and the margin of ducted rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…In addition to Newsome [9], other researchers studied analytical modeling of the buzz phenomenon [10][11][12][13][14][15][16]. Sterbentz et al [10,11] considered a ram jet engine as a Helmholtz resonator and found that the buzz starts if the curve of the intake pressure recovery as a function of mass flow rate has a positive slope greater than a critical value.…”
mentioning
confidence: 99%
“…In addition to Newsome [9], other researchers studied analytical modeling of the buzz phenomenon [10][11][12][13][14][15][16]. Sterbentz et al [10,11] considered a ram jet engine as a Helmholtz resonator and found that the buzz starts if the curve of the intake pressure recovery as a function of mass flow rate has a positive slope greater than a critical value.…”
mentioning
confidence: 99%
“…A pressure-balanced gas regulating system, as given in the study of Shi et al, 23 is depicted in Figure 1. In the diagram, when the gas flow demand rises, the servo valve (2) can make the gas go into the valve head chamber (6) from a gas bottle (1).…”
Section: Model and Control Objectivesmentioning
confidence: 99%
“…Meanwhile, the valve head (5) goes forward along the valve stem (7), which makes the gas generator's (3) pressure rise but its throat area (4) decrease. The reader can refer to the study of Shi et al 23 for further details. The mathematical model of gas flow regulating system for ducted rocket can be described by the following three equations.…”
Section: Model and Control Objectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The anti-regulation of gas flow incites sharply adverse variations of thrust and secondary combustor pressure, which may endanger the stability of the ducted rocket or lead to inlet buzz. [12][13][14] Thus, more attention should be paid on the investigation of the anti-regulation characteristic. Despite much progress in dynamic characteristics of VFDR, no consensus on the physical mechanism of anti-regulation has been achieved yet.…”
Section: Introductionmentioning
confidence: 99%